The role of STING on peroxisome-dependent signalling - Ferreira, Joana Filipa Dias (2017)
Viruses are recognized by several cellular sensors from the innate immune system, activating signalling cascades which result in the production of interferons and other cytokines that affect the virus life cycle and hinder spreading to other cells. Although the RIG-I/MAVS and the STING pathways are assumed to signal, respectively, for RNA and DNA viruses, there is still some controversy on how these pathways interact with and influence each other. The interaction between STING and MAVS, previously reported to take place at mitochondria, supports a crosslink between these pathways. Our group has recently demonstrated that STING is also able to interact with the peroxisomal MAVS. With this work we aimed at studying in more detail the interplay between the STING pathway and the peroxisomal RIG-I/MAVS pathway. One of our approaches involved the knock-down of STING and stimulation of the RIGI/ MAVS pathway in cells that contained MAVS solely at peroxisomes, in order to study the importance of STING for the establishment of an effective peroxisome-dependent antiviral response. In parallel, we activated STING by transfecting 2’3’-cGAMP with the objective of performing RT-qPCR analysis of the peroxisome-dependent production of cytokines. The studies initiated with this thesis will contribute to the unravelling of the interplay between the STING pathways and the peroxisomal-dependent RIG-I/MAVS signalling.